Red And far-red regulation of filament movement correlates with the expression of phytochrome and FHY1 genes in Spirogyra varians (Zygnematales, Streptophyta)1 - Lee, Ji Woong (Journal of phycology, 2019)
© 2019 Phycological Society of America.